BLOUNT DISEASE EVALUATION OF THE OPERATIVE TREATMENT WITHIN 2006-2014 IN DR. SOETOMO GENERAL HOSPITAL SURABAYA - Komang Agung Irianto Suryaningrat; I. G. Ng. Dodo M. Ranuh (Journal Orthopaedi and Traumatology Surabaya)
Background: Blount disease is a growth disturbance of the medial side of the proximal physeal of the tibia, epiphyseal and metaphyseal. Clinically this disease marked by varus angulation and internal rotation of the tibia on the metaphyseal area below knee.